A participatory sustainability assessment for integrated watershed management in urban China. Issue 85 (July 2018) - Brombal, Daniele; Niu, Yuan; Pizzol, Lisa; Moriggi, Angela; Wang, Jingzhi; Critto, Andrea; Jiang, Xia; Liu, Beibei; Marcomini, Antonio
Highlights: IWM in urban China obtains positive results in overcoming the environment-economy divide. This happens at considerable social costs. Social sustainability needs streamlining into China's integrated territorial management. Participatory research must play a role in fostering sustainability of China's integrated territorial management. The methodology employed in the present study can assist in such processes. Abstract: This paper introduces a participatory framework for Sustainability Assessment (SA) for urban Integrated Watershed Management (IWM). The framework is applied to the Lihu Lake Basin (Wuxi City), where between 2002 and 2012 an IWM program was implemented, coordinating water environmental management measures with urban planning. The framework for SA introduced in this paper is based on a Multi-Criteria-Decision-Analysis (MCDA) approach integrating criteria of environmental, economic, and social sustainability. Local stakeholders were engaged in focus group discussions (FGDs) to validate and weigh criteria and attributes employed in the SA framework. Results of the model application indicate that the programme implemented in the Lihu Basin yielded positive results in enhancing environmental conditions, providing more sustainable avenues of environmental management funding, and fostering economic growth. Despite efforts put forward by local authorities, performance of social indicators was comparatively worse, due to relocation policies, increase in housing prices, and scarce public participation. Results show that decision makers pursued viability, rather than comprehensive sustainability.